SPATIAL STUDY OF SOCIAL FACILITIES PLACEMENT IN DENSE SETTLEMENT USING SPACE SYNTAX ANALYSIS CASE STUDY: BANJAR BUALU, BENOA VILLAGE, BALI - Putu Gede Wahyu Satya Nugraha (International Journal of Social Science, 2022)
Banjar Bualu area is one of the densely populated residential areas in Benoa Village, Bali. The high population must be balanced with the number of social facilities to meet the needs for social, cultural, and economic activities of the community. But in reality, there is still a lack of social facilities built to accommodate the social activities of the local community. Social facilities play a role in providing space for socializing and interaction, so their location must be easily accessible from residential areas. This study aims to provide recommendations for the location of social facilities in the Banjar Bualu residential area, Benoa Village. The method used is a qualitative method with an exploratory approach through space syntax analysis with DepthmapX software, to see integration, connectivity, and also the potentials of space that can be used as social facilities. The method of data collection was carried out by non-participant observation and secondary data related to maps of the road network and buildings from settlements in the Banjar Bualu area.